LECTURERS’ STRATEGIES IN ENGLISH SPEAKING CLASS AT UNIVERSITAS MUHAMMADIYAH MAKASSAR - Haris, Nurfareha; Dewi, Ratna; Daddi, Herlina (FKIP Unismuh Makassar, 2024)
This research aimed to find out the differences of the strategies used by both lecturers and to find out the targets that planned to be achieve in using each strategy especially in speaking class at Universitas Muhammadiyah Makassar.The research applied Descriptive Qualitative Method using observation and interview sheet as instrument of the research, the subject in this study was two English speaking lecturers. Subject was taken by using the Purposive Sampling Technique. The data obtained was also analyzed using data reduction, data display, and data verification.Based on the research findings, in teaching speaking, Lecturer A used Presentation and Talks Strategy with the materials “Giving Compliment” and “Making Testimony” with the target students are able to make verbal presentation and used various forms of expression in everyday life. Meanwhile Lecture B also used Presentation and Talks Strategy with the materials “Present Perfect Tense” and “Passive Voice” with the target to make students say something in English with a good grammar and good pronunciation. Lecturer A & B have differences target in teaching English speaking, but they still have a correlation which they wanted to make students speak or talk actively.